2018
DOI: 10.1038/s41598-018-24652-0
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated diamine oxidase originates from extravillous trophoblasts and is decreased in early-onset preeclampsia

Abstract: Human extravillous trophoblast (EVT) invasion of the pregnant uterus constitutes a pivotal event for the establishment of the maternal-fetal interface. Compromised EVT function manifesting in inadequate arterial remodeling is associated with the severe pregnancy disorder early-onset preeclampsia (eoPE). Recent studies suggest that EVTs invade the entire uterine vasculature including arteries, veins and lymphatics in the first trimester of pregnancy. We therefore hypothesized that EVT-derived factors accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Thus, the increased baseline concentration of DAO might be explained by a decreased clearance of DAO in patients with ESLD. The most striking finding of this study was the manifold increase in DAO concentrations during OLT comparable in magnitude to early pregnancy 27 , and the likely resultant inverse correlation between DAO and histamine. The increase in systemic concentration of DAO during OLT can explain the degradation of histamine.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Thus, the increased baseline concentration of DAO might be explained by a decreased clearance of DAO in patients with ESLD. The most striking finding of this study was the manifold increase in DAO concentrations during OLT comparable in magnitude to early pregnancy 27 , and the likely resultant inverse correlation between DAO and histamine. The increase in systemic concentration of DAO during OLT can explain the degradation of histamine.…”
Section: Discussionmentioning
confidence: 49%
“…The increase in systemic concentration of DAO during OLT can explain the degradation of histamine. We have recently shown that plasma levels of DAO (29-52 ng/mL) comparable to those observed in the anhepatic phase can rapidly lower plasma histamine concentrations by ~50-85% within 10 minutes 27 . Thus, the increase in DAO is a mechanistic explanation for the observed decrease in histamine concentrations in patients undergoing OLT.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The development and characterization of the human DAO ELISA was recently published in detail . We tested two commercially available DAO ELISA kits but they were not reliable to measure human DAO …”
Section: Methodsmentioning
confidence: 99%
“…In humans, high DAO mRNA and activity are found in the gastrointestinal tract, kidney, and placenta . Expression in the placenta is restricted to extravillous trophoblast cells and therefore of fetal and not as assumed for decades of maternal origin . Plasma DAO concentrations increase at least 100‐fold during pregnancy, but the physiological function of this rise is not clear.…”
Section: Introductionmentioning
confidence: 99%